Patterns of care and survival outcomes after treatment for uveal melanoma in the post-coms era (2004-2013): a surveillance, epidemiology, and end results analysis - Rao, Yuan James; Sein, Julia; Badiyan, Shahed; Schwarz, Julie K.; DeWees, Todd; Grigsby, Perry; Rao, Prabakar Kumar (Journal of Contemporary Brachytherapy, 2017)
Purpose : The Collaborative Ocular Melanoma Study (COMS) established modern treatment recommendations for uveal melanoma. We aim to evaluate patterns of care and survival outcomes in the time after COMS. Material and methods : The retrospective study population includes 2,611 patients in the SEER database treated for uveal melanoma between 2004-2013. Patients stage were T1-4N0M0. Data analyzed included age, clinical stage, tumor size, race, and treatment. Treatments included enucleation (EN) and globe preserving therapy (GPT), which consisted of limited surgical resection or ablation (LSRA), external beam radiation (EBRT), or brachytherapy (BT). Patients treated with radiation may receive radiation therapy alone (RTA) or radiation therapy and supplemental laser therapy (RT+SLT). We evaluated disease specific survival (DSS) and overall survival (OS) using log-rank statistics, and Cox univariate and multivariate analysis. Results : The median follow-up was 44 months. Treatment strategy was EN in 538 (20.6%) patients, LSRA in 80 (3.1%), EBRT in 609 (23.3%), and BT in 1,384 (53.0%). 1,876 patients received RTA and 117 received RT+SLT. Enucleation was associated with inferior DSS and OS compared to GPT in multivariate analysis (MVA) (p < 0.01). Limited surgical resection or ablation and radiation had similar DSS and OS. Brachytherapy and EBRT had similar DSS and OS. Radiation therapy and supplemental laser therapy was associated with improved DSS compared to RTA in UVA (p = 0.03), but not MVA. The 5-year DSS for enucleation, RTA, and RT+SLT were 66.7%, 87.0%, and 94.7% (p < 0.01), respectively. Conclusions : Globe preserving treatments such as limited surgery or radiation are commonly utilized alternatives to enucleation, and resulted in favorable survival outcomes. Additional research is required to compare the outcomes of the various globe preserving treatment strategies.